2018
DOI: 10.1016/j.jbiomech.2018.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Midtarsal locking, the windlass mechanism, and running strike pattern: A kinematic and kinetic assessment

Abstract: Changes in running strike pattern affect ankle and knee mechanics, but little is known about the influence of strike pattern on the joints distal to the ankle. The purpose of this study was to explore the effects of forefoot strike (FFS) and rearfoot strike (RFS) running patterns on foot kinematics and kinetics, from the perspectives of the midtarsal locking theory and the windlass mechanism. Per the midtarsal locking theory, we hypothesized that the ankle would be more inverted in early stance when using a FF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
55
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(60 citation statements)
references
References 33 publications
4
55
1
Order By: Relevance
“…In Sanchis-Sales et al (2016) study, ground reaction force was attributed to each foot segment (hindfoot, forefoot and hallux) through the use of a pressure sensitive mat, which may contribute to the minor differences seen in our data. In runners with rearfoot strike patterns, Bruening et al (2018) found midtarsal joint quasi-stiffness values of 0.41 ± 0.11 Nm/kg°, which are understandably higher than the values in this study due to the more demanding running task. In order to explore mechanisms which might be associated with midtarsal quasi-stiffness, a secondary analysis was conducted.…”
Section: Discussioncontrasting
confidence: 90%
“…In Sanchis-Sales et al (2016) study, ground reaction force was attributed to each foot segment (hindfoot, forefoot and hallux) through the use of a pressure sensitive mat, which may contribute to the minor differences seen in our data. In runners with rearfoot strike patterns, Bruening et al (2018) found midtarsal joint quasi-stiffness values of 0.41 ± 0.11 Nm/kg°, which are understandably higher than the values in this study due to the more demanding running task. In order to explore mechanisms which might be associated with midtarsal quasi-stiffness, a secondary analysis was conducted.…”
Section: Discussioncontrasting
confidence: 90%
“…The metatarsophalangeal joints function as a dissipater of large amounts of energy during running and sprinting, particularly when a passive dorsiflexion occurs at the foot contact transition from the metatarsal heads onto the toes, but fail to generate any energy at push off by remaining in that position (Stefanyshyn and Nigg, 1997). Since the less experienced runners displayed larger angles of hallux dorsiflexion during this transition between midstance to push off, they would be expected to have greater soft tissue tension, such as in the toe flexor muscles and tendons, and plantar fascia (Bruening et al, 2018). However, since there was little or no metatarsophalangeal plantar flexion, there was more energy dissipated by the passive structures, leading to less efficient propulsion in the following phase.…”
Section: Discussionmentioning
confidence: 99%
“…The similarity may arise from the fact that both models include the MTP joint, because hopping requires a considerable MTP joint range of motion, which is captured by the 3MFM and 5MFM. An additional, albeit slightly unrelated consideration, is that the presence of the MTP joint may also better capture intrinsic foot mechanics such as the windlass mechanism, which occurs with dorsiflexion of the MTP joint, increases plantar fascia tension, and transitions the arch from compliant to rigid and generates propulsion . Thus, the MTP joint in 3MFM and 5MFM may better capture the range of motion and perhaps other intrinsic muscle mechanisms.…”
Section: Discussionmentioning
confidence: 99%